Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s11606-013-2382-8
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use and Clinical Osteoarthritis in the General Population: A Longitudinal Study

Abstract: BACKGROUNDOne hypothesis has posited whether abnormal lipid metabolism might be a causal factor in the pathogenesis of osteoarthritis (OA). Routine statin use in clinical practice provides the basis for a natural experiment in testing this hypothesis.OBJECTIVETo test the hypothesis that statins reduce the long-term occurrence of clinically defined OA.DESIGNCohort design with a 10-year follow-up.PARTICIPANTS16,609 adults cardiovascular disease cohorts aged 40 years and over from the UK General Practice Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 32 publications
2
70
0
Order By: Relevance
“…Riddle et al found no association between statin use and knee pain in a sample of 2,207 men and women with or at high risk of OA (12). However, 2 studies that examined associations between statin use and symptomatic radiographic OA did find significant associations (9,10). In these 2 studies, more frequent use and higher dose were associated with reduced risks of symptomatic radio- 16 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Riddle et al found no association between statin use and knee pain in a sample of 2,207 men and women with or at high risk of OA (12). However, 2 studies that examined associations between statin use and symptomatic radiographic OA did find significant associations (9,10). In these 2 studies, more frequent use and higher dose were associated with reduced risks of symptomatic radio- 16 …”
Section: Discussionmentioning
confidence: 99%
“…graphic OA (9,10). A potential explanation for the lack of an association between statin use and joint pain/stiffness is that our question was not specific enough.…”
Section: Peeters Et Almentioning
confidence: 93%
See 2 more Smart Citations
“…1 However, the data also contributes to a growing evidence base supporting the pleiotropic effects of statins, which has been a topic of interest for vascular biologists and clinicians alike. Clearly, the potential public health impact of increasing the use of these well-established agents is vast.…”
mentioning
confidence: 94%